2021
DOI: 10.13189/eer.2021.090301
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Seasonal Box Jenkins-ANN Approach for Water Level Forecasting in Thailand

Abstract: Every year, many basins in Thailand face the perennial droughts and floods that lead to the great impact on agricultural segments. In order to reduce the impact, water management would be applied to the critical basin, for instance, Yom River basin. An importing task of management is quantitative prediction of water that is stated by water level. This study proposes the hybridized forecasting models between the stochastic approaches, seasonal autoregressive integrated moving average (SARIMA) models and machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this research, thanks to an expert, the essential elements were: former users' benefit, new users' benefit, sewerage works investment, drinking water works investment, population growth, inflation, sewerage operation, and maintenance costs, and drinking water operation and maintenance works. Of course, this is a simplified model since, for drinking water works, other elements, as stated by [33], are necessary. After that, the distribution of the variable was selected depending on the variables' data nature.…”
Section: Methodsmentioning
confidence: 99%
“…In this research, thanks to an expert, the essential elements were: former users' benefit, new users' benefit, sewerage works investment, drinking water works investment, population growth, inflation, sewerage operation, and maintenance costs, and drinking water operation and maintenance works. Of course, this is a simplified model since, for drinking water works, other elements, as stated by [33], are necessary. After that, the distribution of the variable was selected depending on the variables' data nature.…”
Section: Methodsmentioning
confidence: 99%
“…In the mid-20th century, vinyl records became the dominant format for music distribution. Record labels competed to sign popular artists and released albums on vinyl, which were sold in record stores [13]. Physical distribution channels played a crucial role in the success of artists and albums.…”
Section: Background Of the Music Industrymentioning
confidence: 99%
“…Hybridisation has emerged as a promising technique for overcoming numerous drawbacks of standalone methods while also improving prediction accuracy (Hajirahimi & Khashei, 2022). There are several types of hybrid models, e.g., the hybrid model that combines a physical model and a machine learning model (Nualtong et al, 2021;Xu et al, 2019), and the hybrid stochastic-ML model proposed by Koutsoyiannis and Montanari (Koutsoyiannis & Montanari, 2022). Papacharalampous (Papacharalampous et al, 2019) showed that the hybrid stochastic-ML model is better than single stochastic or ML models.…”
Section: Introductionmentioning
confidence: 99%